ANALISIS BEBERAPA ASPEK REPRODUKSI KEPITING BAKAU (SCYLLA SERRATA) DI PERAIRAN SEGARA ANAKAN, KABUPATEN CILACAP, JAWA TENGAH - Hadun Asmara; Etty Riani; Agus Susanto (LPPM Universitas Terbuka, 2011)
Research was done in Segara Anakan water lagoon, Cilacap District, Central Java, from September 2003 to November 2003. Samples of mangrove crab were taken using catching tool of wadong and pintur which setted in the afternoon and unsetted the next morning. From all samples collected, there were 55 male and 113 female crabs. The width range of male shells were 31.5-122.5 mm and weight range were 53.75-286.08 gram, while the females shells have width range of 78.4-120.5 mm and weight range of 69.38-229.08 gram. Fecundity of mangrove crabs (Scylla serrata) ranges between 345,923-1,472,639 eggs with mean value of 646.194. Diameter of the egg curve shows that the mangrove crabs were total spawner, which means totally discharge their eggs.